2023
DOI: 10.1021/acsaenm.3c00093
|View full text |Cite
|
Sign up to set email alerts
|

Bimetallic In–Sn Core–Shell Catalyst Enabling Highly Efficient Electrocatalytic CO2 Reduction to Formate

Abstract: Bimetallic catalysts are ideal candidates for boosting electrochemical CO 2 reduction reaction (CO 2 RR). However, these catalysts have largely relied on tedious synthesis technology and play electrolytic role with the help of a metal substrate or gas diffusion electrode. Herein, noble metal-free In−Sn nanoparticles (NPs) with a core−shell structure that contains a hybrid In−Sn core and native Sn-doped In 2 O 3 shell have been successfully grown on the copper foam by the potential-driven volume diffusion strat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Similarly, the N 1s spectrum also did not show any NO-related peaks on the Bi/Cu foam catalyst surface (as shown in Figure S10e). In the case of In/Cu-f, the catalyst was exposed to pure CO 2 for 5 h. XPS characterization was performed before and after the reaction; the deconvoluted In 3d spectrum confirms that the In/Cu-f catalyst surface existed in both In(OH) 3 (445.03 and 452.57 eV) and In 2 O 3 (444.30 and 451.84 eV) states before CO 2 reduction , as shown in Figure d. However, after the reaction, the catalyst surface turned In (443 eV) and In 2 O 3 (451.3 eV).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, the N 1s spectrum also did not show any NO-related peaks on the Bi/Cu foam catalyst surface (as shown in Figure S10e). In the case of In/Cu-f, the catalyst was exposed to pure CO 2 for 5 h. XPS characterization was performed before and after the reaction; the deconvoluted In 3d spectrum confirms that the In/Cu-f catalyst surface existed in both In(OH) 3 (445.03 and 452.57 eV) and In 2 O 3 (444.30 and 451.84 eV) states before CO 2 reduction , as shown in Figure d. However, after the reaction, the catalyst surface turned In (443 eV) and In 2 O 3 (451.3 eV).…”
Section: Resultsmentioning
confidence: 99%
“…One strategy to enhance catalyst properties is to utilize synergetic metals. Synergistic bimetallic electrocatalysts can have a promising avenue for improving activity and selectivity compared to their monometallic counterparts by fine-tuning their structure, morphology, and composition. Bimetallic electrocatalysts, such as In–Bi, Zn–Bi, Sn–Cu, Bi–Eu, Pd–Bi, Bi–Sb, Sn–In, and Sn–Zn, have demonstrated to promote the conversion of CO 2 to formate/FA. Recently, Liu et al reported bimetallic Sn–Cu electrocatalyst showing over 80% FE; however, the performance was limited to 20 h and higher overpotential (−1.11 V vs RHE) .…”
Section: Introductionmentioning
confidence: 99%
“…It is also a promising candidate as a liquid hydrogen carrier with the capability of releasing gaseous hydrogen under mild conditions (e.g., at relatively low temperatures of 60–80 °C) . At present, several types of post-transition metal-based electrocatalysts, including Sn-, In-, Pb-, Pd-, and Bi-based electrocatalysts, have been developed for the CO 2 -to-formate conversion with successive progress. Nevertheless, a large overpotential of up to 1.0 V is generally required to reach the industry-scale current densities (e.g., ≥200 mA cm –2 ), in addition to the pending issues of the insufficient Faradaic efficiency (FE), poor catalyst durability, and environmental toxicity. …”
Section: Introductionmentioning
confidence: 99%